Comparison of Anatomic Landmarks and Ultrasound Guidance for Intercostal Nerve Injections in Cadavers. Issue 6 (1st November 2013) - Bhatia, Anuj; Gofeld, Michael; Ganapathy, Sugantha; Hanlon, John; Johnson, Marjorie
Abstract : Background and Objectives: Intercostal nerve (ICN) injections are routinely performed under anatomic landmark or fluoroscopic guidance for acute and chronic pain indications. Ultrasound (US) is being used increasingly to perform ICN injections, but there is lack of evidence to support categorically the benefits of US over conventional techniques. We compared guidance with US versus anatomic landmarks for accuracy and safety of ICN injections in cadavers in a 2-phase study that included evaluation of deposition of injected dye by dissection and spread of contrast on fluoroscopy. Methods: A cadaver experiment was performed to validate US as an imaging modality for ICN blocks. In the first phase of the study, 12 ICN injections with 2 different volumes of dye were performed in 1 cadaver using anatomic landmarks on one side and US-guidance on the other (6 injections on each side). The cadaver was then dissected to evaluate spread of the dye. The second phase of the study consisted of 74 ICN injections (37 US-guided and 37 using anatomic landmarks) of contrast dye in 6 non-embalmed cadavers followed by fluoroscopy to evaluate spread of the contrast dye. Results: In the first phase of the study, the intercostal space was identified with US at all levels. Injection of 2 mL of dye was sufficient to ensure compete staining of the ICN for 5 of 6 US-guided injections but anatomic landmark guidance resulted in correct injection at only 2 of 6 intercostal spaces. No intravascular injection was found on dissection with either of the guidance techniques. In the second phase of the study, US-guidance was associated with a higher rate of intercostal spread of 1 mL of contrast dye on fluoroscopy compared with anatomic landmarks guidance (97% vs 70%; P = 0.017). Conclusions: Ultrasound confers higher accuracy and allows use of lower volumes of injectate compared with anatomic landmarks as a guidance method for ICN injections in cadavers. Ultrasound may be a viable alternative to anatomic landmarks as a guidance method for ICN injections.